Sexual Education In Malaysia: Accepted Or Rejected? - Siti Syairah Mohd Mutalip; Ruzianisra Mohamed (Tehran University of Medical Sciences, 2012)
Background: Introduction to sexual education in schools was suggested by the Malaysian government as one of the effort taken in the aim to reduce the sexual-related social problems among Malaysian teenagers nowadays. This study was proposed in the aim to determine the rate of acceptance among adolescents on the implementation of sexual education in schools.Methods: This study was conducted using questionnaires distributed to 152 pre-degree students in Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), Kampus Puncak Alam, Selangor, Malaysia. Obtained data were statistically analyzed.Results: Almost half (49.3%) of the respondents agreed that sexual education might help to overcome the social illness among school teenagers. Besides, a large number (77.6%) of respondents also agreed that this module should be incorporated with other core subjects compare to the feedback received on the implementation of this module on its own (28.9%).Conclusion: These results have provided some insight towards the perception of sexual education among the teenagers. Since most of the respondents agreed with this idea, so it might be a sign that the implementation of sexual education is almost accepted by the adolescents.